2017
DOI: 10.1002/1878-0261.12142
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐661 modulates redox and metabolic homeostasis in colon cancer

Abstract: Cancer cell survival and metastasis are dependent on metabolic reprogramming that is capable of increasing resistance to oxidative and energetic stress. Targeting these two processes can be crucial for cancer progression. Herein, we describe the role of microRNA‐661 (miR661) as epigenetic regulator of colon cancer (CC) cell metabolism. MicroR661 induces a global increase in reactive oxygen species, specifically in mitochondrial superoxide anions, which appears to be mediated by decreased carbohydrate metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Here, our findings suggested that on miR-539 might be a tumor promoter in contrast to previous experimental studies. On the other hand, prior studies showed that miR-661 was a tumor promoter in non-small cell lung cancer, colon cancer and ovarian cancer [55][56][57]. However, the roles of miR-661 in HCC development has not been investigated.…”
Section: Plos Onementioning
confidence: 99%
“…Here, our findings suggested that on miR-539 might be a tumor promoter in contrast to previous experimental studies. On the other hand, prior studies showed that miR-661 was a tumor promoter in non-small cell lung cancer, colon cancer and ovarian cancer [55][56][57]. However, the roles of miR-661 in HCC development has not been investigated.…”
Section: Plos Onementioning
confidence: 99%
“…Dysregulated expression of multiple rate-limiting enzymes may lead to activation of the Warburg effect in cancer [7][8][9]. Previous evidence indicated that altered metabolic genes or miRNAs modulate metabolic homeostasis in CC [10][11][12]. Moreover, abnormal changes in this signaling pathway direct a metabolic program of glycolysis in CC [13].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 27 ] found that miR-206 induces ROS accumulation in vivo and in vitro by binding to SOD1 mRNA, which may be a cause of cardiovascular disease. Gómez de Cedrón et al [ 28 ] reported that miR-661 regulates redox and metabolic homeostasis in colon cancer. Therefore, it is noteworthy to reveal the multidimensional regulatory network in tumor genesis and progression of prognosis-related RRGs and miRNAs in this study.…”
Section: Resultsmentioning
confidence: 99%